Chemical reactivity of group 14 [E9]4– and 15 [E'7]3– Zintl ions - Espinoza Quintero, G (2015)
This thesis describes the reactivity of Zintl ions of groups 14 [E9]4– (E = Ge and Sn)and 15 [E'7]3– (E' = P and As) towards a number or transition, post-transition and main group reagents. The synthesis and characterisation of the resulting novel cluster anions is described herein. Coordination compounds of group 14 Zintl ions were synthesised when K4Ge9 was reacted with Zn[N(SiMe3)2]2 to give the simple coordination compound [Ge9ZnN(SiMe3)2]3–. The heavier analogue K4Sn9 reacts with the same metal precursor to give the paramagnetic species [Sn9ZnNSiMe3]3– where a trimethylsilyl group has been lost. K4Ge9 reacts with [Ru(COD)(η3-CH2C(CH3)CH2)2] to form the paramagnetic endohedral compound [Ru@Ge12]3– and with [Co(PEt2Ph)2(mes)2] to form the prolate endohedral compound [Co2@Ge16]4–, which has two metal centres encapsulated inside the sixteen atom germanium cage. Regarding group 15 Zintl ion reactivity, the reactions between pyridine solutions of [HP7]2– and E[N(SiMe3)2]2 (E = Ge, Sn and Pb) have been found to yield coordination compounds of the type [P7E(N(SiMe3)2]2–. The germanium containing species [P7GeN(SiMe3)2]2– quickly decomposes at room temperature to give rise to the thermodynamic product [(P7)2Ge2N(SiMe3)2]3–, a process that involves the loss of an amide moiety. Activation products were also synthesised from the reaction of [E'7]3– with varying stoichiometries of VCp2. The reaction with 0.7 equivalents of VCp2 yields the sandwich complexes [CpV(η5-E'5)]n– (E' = P: n = 1; E' = As, n = 1 and 2) whereas with 2.5 equivalents the products are the triple-decker sandwich complexes [(CpV)2(ηx-E'x)]– (E' = P: x = 6; E' = As: x = 5).